Implementing poultry vaccination and biosecurity at the village level in Tanzania: a social strategy to promote health in free-range poultry populations - Msoffe, Peter L. M. (Springer Netherlands, 2009)
A social strategy was tested for implementing Newcastle disease (ND) vaccination and biosecurity improvements among free-ranging chicken at village level in Tanzania. In addition to training the local poultry vaccinators, data recorders and poultry-keepers, the strategy involved training and empowering leaders at the district, ward and village level. The trainings covered poultry health, management, and marketing of village chickens, with an emphasis on ND vaccination and improving biosecurity against avian influenza (AI), The study sites included villages in one ward in each of three each three districts (Iringa, Mtwara-Mikindani, and Mvomero) of mainland Tanzania. Ninety-six local leaders at district level and 101 leaders at ward levels were trained. In addition, 196 farmers (households) were trained, as well as 86 vaccinators and 26 data recorders. Data recorders were also trained as poultry first aid workers. ND vaccination was conducted by the vaccinators, supervised by their local leaders with technical assistance from veterinarians. A total of 158,343 village chickens were vaccinated in three rounds of vaccination three months apart. The training and empowerment of local leaders and local implementers was the key element for success as it fostered the feeling of local ownership of the program and prevented conflicts with other development activities within the villages. We conclude that most animal health programs will increase their odds of success by involving local leaders and by addressing the current challenges facing the farmers. Further assessment on the usefulness of this approach is needed.